(untitled) (Journal of history, 2025)
In the history of Kazakhstan, the last quarter of the 19th - early 20th century is the time of active penetration of imperial structures and ideas into the territory of the Steppe. One of the key areas through which the Russian Empire sought to implement its policy of social transformation and modernization of the Kazakh traditional society was education. The article will focus on Kazakh graduates of the Omsk and Semipalatinsk teacher’s seminaries, who, according to the plan of the imperial authorities, were to become conductors of the ideas of unification in the territory of the Akmola and Semipalatinsk regions, but eventually became pioneers of national education. The purpose of this publication, based on the identified archival and printed materials, is not only to restore the names of these people, but also to rethink their role in the history of the Kazakh people. The author is the first to introduce into scientific circulation the names and facts from the biographies of Kazakh graduates of the Omsk and Semipalatinsk Teachers’ Seminaries, systematizing them in the prosopography format. The scientific and practical significance of the study lies in identifying and systematizing names that were previously little known or were not combined into a single database. This allows researchers to get an idea of ​​the social structure of this group, their origin, subsequent career and participation in the events of the early twentieth century. The work is based on the application of the historical and genetic method to study the process of creating the Omsk and Semipalatinsk Teachers’ Seminaries in the West Siberian Educational District, their goals and influence on the formation of the Kazakh intelligentsia. Of great importance was the historical and chronological method, which made it possible to identify common features and characteristics in the social characteristics of the students of these seminaries. By analyzing the life path of these people, the article reveals how they, being initially a product of the imperial unification policy, became catalysts for national education, laying the foundations of the Kazakh intelligentsia. The names of 20 Kazakh graduates of the Omsk Teachers’ Seminary (1872-1919) and 26 Kazakh students of the Semipalatinsk Teachers’ Seminary (1903-1920) are revealed. Thus, the value of the study is that it not only fills the gaps in our understanding of the personalities, but also helps in creating a holistic systemic picture of the number of Kazakh graduates of educational institutions of the Russian Empire in the context of socio-political transformations in the Steppe in the late 19th - early 20th centuries.